Evaluating the Safety and Efficacy of Developed Restora™ Clot Retrieval Device in a Porcine Model - Gautam, Khushbu D; Kumar, Kothwala Dr. Devesh; Khusboo, Shah; Kamna, Pandya; Trupti, Patel G.; Arpit, Dave; Hrishikesh, Shah (International Journal of Innovative Research in Medical Science, 2024)
The study evaluated the safety and performance of a new Clot Retrieval Device in a porcine model using three female swine. These swine were fasted overnight without water and kept NPO (nil per os) for six hours post-recovery. They received Aspirin and Clopidogrel for three days before the procedure, continuing with a reduced dose of aspirin post-implantation until sacrifice. Physical examination ensured that the swine met study criteria, followed by anesthesia and monitoring with Ketamine, Xylazine, Propofol, and inhalation anesthesia. Areas for femoral vein access and ECG lead application were shaved, and Atropine was given to control respiratory discharges. On the first day, two swine (P1 and P2) had clots implanted and retrieved using the Clot Retrieval Device. The third pig (P3) also had clots implanted, with retrieval on the procedural day and extended monitoring to day 30. Two types of clots (autologous and synthetic) were placed in each pig and retrieved under heparinization, with angiography and measurements conducted before and after implantation. Histopathological evaluations were done on harvested veins: P1 and P2 on day 0 and P3 on Day 30. The autologous clot was successfully retrieved in all cases, while the synthetic clot remained but did not cause clinical signs. Results demonstrated that the clot retrieval device effectively and safely retrieved autologous clots without injuring targeted arteries, and no clot-related lesions were found in the internal carotid arteries. Swine were monitored for health parameters such as body weight, morbidity, and mortality, with no significant changes or adverse effects observed. Pathological examinations included clinical pathology, necropsy, and histopathology. The study concluded that the clot retrieval device was effective and safe for retrieving autologous clots in a porcine model, suggesting its potential safe use in clinical settings.